TBK1 is paradoxical in tumor development: a focus on the pathway mediating IFN-I expression - Wang, Banglu; Zhang, Fan; Wu, Xiaoyu; Ji, Mei (Frontiers in Immunology, 2024)
TANK-binding kinase 1 (TBK1) is a member of the IKK family and plays a crucial role in the activation of non-canonical NF-κB signaling and type I interferon responses. The aberrant activation of TBK1 contributes to the proliferation and survival of various types of tumor cells, particularly in specific mutational or tumorous contexts. Inhibitors targeting TBK1 are under development and application in both in vivo and in vitro settings, yet their clinical efficacy remains limited. Numerous literatures have shown that TBK1 can exhibit both tumor promoting and tumor inhibiting effects. TBK1 acts as a pivotal node within the innate immune pathway, mediating anti-tumor immunity through the activation of innate immune responses. Facilitating interferon-I (IFN-I) production represents a critical mechanism through which TBK1 bridges these processes. IFN has been shown to exert both beneficial and detrimental effects on tumor progression. Hence, the paradoxical role of TBK1 in tumor development may necessitate acknowledgment in light of its downstream IFN-I signaling cascade. In this paper, we review the signaling pathways mediated by TBK1 in various tumor contexts and summarize the dual roles of TBK1 and the TBK1-IFN pathways in both promoting and inhibiting tumor progression. Additionally, we highlight the significance of the TBK1-IFN pathway in clinical therapy, particularly in the context of immune response. We anticipate further advancements in the development of TBK1 inhibitors as part of novel cancer treatment strategies.